Systemic lupus erythematosus-related acute pancreatitis: An uncommon clinical manifestation - Mahur , Hemant Kumar; Jain, Neha; Mittal, Dheeraj; Agarwal, Arpit; Labana, Daksh; Bankal, Yashu (Indian Journal of Case Reports, 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with diverse clinical manifestations, ranging from mild to life-threatening complications. Acute pancreatitis (AP) is a rare but serious manifestation of SLE, occurring in